PENERPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING PADA MATERI STOIKIOMETRI KELAS X.2 SMAN 5 MATARAM TAHUN AJARAN 2022/2023 - Samsul Bahri; Andriana Andriana; Amanda Eki Wirya Sati; Nursyahraini Nursyahraini (JURNAL ASIMILASI PENDIDIKAN, 2023)
The purpose of this study was to determine the improvement of students' problem-solving skills through the application of the discovery learning model and evaluate the effect of the application of the discovery learning model on improving students' problem-solving skills in stoichiometry material in class X.2 SMAN 5 Mataram. The research method used is Classroom Action Research (PTK) which generally consists of three cycles. Each cycle has four stages, namely planning, action, observation, and reflection. This research was conducted in class X-2 SMAN 5 Mataram which amounted to 35 students. This study focused on stoichiometry material which includes the concept of moles in relation to concentration; limiting reactions; and molecules and empirical formulas. The data collection techniques used were formative tests, observation sheets, and documentation. From the research results obtained 88.57% of students have reached completeness in achieving indicators on problem solving skills in cycle III. So, using the discovery learning model is effective enough to improve students' problem-solving skills.